Expression of ESE-3 isoforms in immunogenic and tolerogenic human monocyte-derived dendritic cells. - Florian Sprater; Arnt-Ove Hovden; Silke Appel (PLoS ONE, 2012)
Dendritic cells (DC) are the only hematopoietic cells expressing the epithelial specific Ets transcription factor ESE-3. Here we analyzed presence and quantity of isoforms ESE-3a, ESE-3b and ESE-3j in various immunogenic and tolerogenic human monocyte-derived DC (moDC) and blood DC populations using quantitative real time PCR and immunoblot analyses. ESE-3a and ESE-3b were detectable in all moDC populations with ESE-3b being the main transcript. ESE-3b expression was upregulated in immunogenic moDC and downregulated in tolerogenic moDC compared to immature moDC. ESE-3a had similar transcript levels in immature and immunogenic moDC and had very low levels in tolerogenic moDC. In blood DC populations only splice variant ESE-3b was detectable. ESE-3j was not detectable in any of the DC populations. These findings suggest that ESE-3b is the functionally most important ESE-3 isoform in DC.